2006
DOI: 10.4049/jimmunol.176.5.3215
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the Transcription Factor Foxp3 Converts Desmoglein 3-Specific Type 1 Regulatory T Cells into Th2-Like Cells

Abstract: Pemphigus vulgaris (PV) is a severe autoimmune bullous skin disorder and is associated with autoantibodies against desmoglein (Dsg)3 that are regulated by Th2 cells. Recently, Dsg3-specific type 1 regulatory T cells (Tr1) were identified that are presumably critical for the maintenance of tolerance against Dsg3 because there is a much lower Dsg3-specific Tr1:Th2 ratio in the PV patients than in healthy individuals. The aim of this study was to down-regulate the transcription factor Foxp3 in Dsg3-specific Tr1 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 54 publications
7
46
0
2
Order By: Relevance
“…In contrast, it has been recently reported that human Tr1 cell clones specific for desmoglein3, the dominant autoantigen in pemphigus vulgaris, constitutively express FOXP3 [31]. Interestingly, silencing of FOXP3 expression resulted in a shift from Tr1 towards a Th2-like phenotype and the loss of the ability to suppress Teff cells in vitro [31]. The reason for these controversial results on the role of FOXP3 expression in Tr1 cell suppressor function in vitro remains to be elucidated.…”
Section: Foxp3 and Adaptive T Regulatory Type 1 (Tr1) Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, it has been recently reported that human Tr1 cell clones specific for desmoglein3, the dominant autoantigen in pemphigus vulgaris, constitutively express FOXP3 [31]. Interestingly, silencing of FOXP3 expression resulted in a shift from Tr1 towards a Th2-like phenotype and the loss of the ability to suppress Teff cells in vitro [31]. The reason for these controversial results on the role of FOXP3 expression in Tr1 cell suppressor function in vitro remains to be elucidated.…”
Section: Foxp3 and Adaptive T Regulatory Type 1 (Tr1) Cellsmentioning
confidence: 97%
“…Functional suppressor Tr1 cells can be differentiated in vitro from naive T cells of IPEX patients lacking FOXP3 [30], demonstrating that Tr1 cells do not require FOXP3 to mediate their suppressor activity. In contrast, it has been recently reported that human Tr1 cell clones specific for desmoglein3, the dominant autoantigen in pemphigus vulgaris, constitutively express FOXP3 [31]. Interestingly, silencing of FOXP3 expression resulted in a shift from Tr1 towards a Th2-like phenotype and the loss of the ability to suppress Teff cells in vitro [31].…”
Section: Foxp3 and Adaptive T Regulatory Type 1 (Tr1) Cellsmentioning
confidence: 97%
“…ture of human Tr1s specific for Dsg3 (56). These Dsg3-specific Tr1s expressed phenotypic markers of Tregs such as cytotoxic T cell antigen-4, glucocorticoid-induced TNF receptor, and membrane-bound TGF-β and inhibited the activation of autoreactive Th1 and Th2 cells via the secretion of IL-10 and TGF-β ( Figure 5).…”
Section: Figurementioning
confidence: 99%
“…Clinically, a deficiency in Treg function or decrease in the proportion of Treg has been observed to influence the pathogenesis of collagen or autoimmune diseases such as multiple sclerosis (9), rheumatoid arthritis (10), systemic lupus erythematosus (II), and pemphigus vulgaris (12). These findings at the cellular and molecular levels provide firm evidence that CD4+CD25+FoxpY regulatory T cells are an indispensable cellular constituent of the normal immune system, and that these cells play crucial roles in establishing and maintaining immunologic self-tolerance and immune homeostasis.…”
mentioning
confidence: 99%